2013
DOI: 10.9790/3008-0735765
|View full text |Cite
|
Sign up to set email alerts
|

Production, Optimization, Purification, Testing Anti-Microbial and Dye Decolorizing Properties of Penicillin G Acylase from Penicillium chrysogenum.

Abstract: Abstract:The enzyme Penicillin G Acylase (PGA)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…In comparison to the SPG isolates, others found that the closely related species of P. chrysogenum and P. brevicompactum from continental environments grew in the range of 5 to 37 • C, and optimally at 25 to 30 • C (Pitt, 1973;Magan and Lacey, 1984;Sautour et al, 2001;Mahendiran et al, 2013). Additionally, fungi from shallow marine sediments were found to also be mesophilic and psychrotolerant (Singh et al, 2010).…”
Section: Identification and Characterization Of Spg Fungimentioning
confidence: 99%
“…In comparison to the SPG isolates, others found that the closely related species of P. chrysogenum and P. brevicompactum from continental environments grew in the range of 5 to 37 • C, and optimally at 25 to 30 • C (Pitt, 1973;Magan and Lacey, 1984;Sautour et al, 2001;Mahendiran et al, 2013). Additionally, fungi from shallow marine sediments were found to also be mesophilic and psychrotolerant (Singh et al, 2010).…”
Section: Identification and Characterization Of Spg Fungimentioning
confidence: 99%